2022
DOI: 10.1021/acs.jafc.2c00468
|View full text |Cite
|
Sign up to set email alerts
|

Study on Absorption, Distribution, Metabolism, and Excretion Properties of Novel Insecticidal GABA Receptor Antagonist, Pyraquinil, in Diamondback Moth Combining MALDI Mass Spectrometry Imaging and High-Resolution Mass Spectrometry

Abstract: A thorough understanding of absorption, distribution, metabolism, and excretion (ADME) of insecticide candidates is essential in insecticide development and structural optimization. Here, ADME of pyraquinil, a novel insecticidal GABA receptor antagonist, in Plutella xylostella larvae during the accumulation phase and depuration phase was investigated separately using a combination of UHPLC-Q-Orbitrap, HPLC-MS/MS, and MALDI-MSI. Five new metabolites of pyraquinil were identified, and a metabolic pathway was pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 48 publications
(87 reference statements)
1
7
0
Order By: Relevance
“…Three of the detected TPs of pyraquinil, namely TP558, TP544, and TP500, have been reported in our previous study . It was confirmed that TP558 was formed by oxidation of the trifluoromethylsulfinyl (−SOCF 3 ) group, and TP544 was identified as the carboxylic derivative of TP558.…”
Section: Resultssupporting
confidence: 68%
See 1 more Smart Citation
“…Three of the detected TPs of pyraquinil, namely TP558, TP544, and TP500, have been reported in our previous study . It was confirmed that TP558 was formed by oxidation of the trifluoromethylsulfinyl (−SOCF 3 ) group, and TP544 was identified as the carboxylic derivative of TP558.…”
Section: Resultssupporting
confidence: 68%
“…32−34 However, as a new pesticide, previous studies on pyraquinil were mainly focused on its synthesis method, 35−37 insecticidal activity, 25,28 mode of action, 26,27 and toxicokinetics. 38 To date, the only existing research related to environmental behavior has been the establishment of the stereoselective analytical methods of pyraquinil isomers in vegetables. 39 Research on the degradation kinetics, potential TPs, and degradation pathways of pyraquinil in water has not yet been reported.…”
Section: Introductionmentioning
confidence: 99%
“…The γ-aminobutyric acid receptor (GABAR) is an important pesticide target with four distinct coupled binding sites that are associated with high selectivity and limited cross-resistance. Currently, there are various types of chemical noncompetitive antagonists (NCAs) that target GABAR. Isoxazoline drugs with an active core skeleton of 3,5-diphenyl-5-(trifluoromethyl)-4,5-dihydroisoxazole are the second generation of NCAs. They kill insects by blocking the inward current of chloride ions through ionotropic GABAR (iGABAR) channels, which disrupts the nervous system and causes hyperexcitation.…”
Section: Introductionmentioning
confidence: 99%
“…However, the continuous insecticide application has frequently raised environmental problems and developed insecticide resistance to insect pests (Horowitz et al, 2020; Kueh Tai et al, 2022; Lin et al, 2022; Lokeshwari et al, 2016). The thickening or alteration of the cuticle composition, improved drug excretion and mutation of insecticide target sites contribute to increased insect pesticide resistance (Balabanidou et al, 2018; Casida & Durkin, 2013; Wan et al, 2022). Furthermore, various studies have reported that insect symbiotic microorganisms are involved in the host resistance by degrading pesticides or altering host metabolism (Blanton & Peterson, 2020; Chen et al, 2020; Kikuchi et al, 2012; Pang et al, 2018; Sato et al, 2021).…”
Section: Introductionmentioning
confidence: 99%